2018
DOI: 10.1103/physrevmaterials.2.032001
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal Coulomb correlations in pure and electron-doped Sr2IrO4 : Spectral functions, Fermi surface, and pseudo-gap-like spectral weight distributions from oriented cluster dynamical mean-field theory

Abstract: We address the role of non-local Coulomb correlations and short-range magnetic fluctuations in the high-temperature phase of Sr2IrO4 within state-of-the-art spectroscopic and first-principles theoretical methods. Introducing a novel cluster dynamical mean field scheme, we compute momentumresolved spectral functions, which we find to be in excellent agreement with angle-resolved photoemission spectra. We show that while short-range antiferromagnetic fluctuations are crucial to account for the electronic propert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 70 publications
2
29
0
Order By: Relevance
“…As can be seen from the band structure, figure 3, the position of the conduction band minimum always occurs at the M point regardless of the strain. The occurrence of the conduction minimum at M is consistent with the measured Fermi surface in the electron doped case, where an elliptical shaped Fermi surface has been seen [8].…”
Section: Strain Induced X Gcrossoversupporting
confidence: 87%
See 1 more Smart Citation
“…As can be seen from the band structure, figure 3, the position of the conduction band minimum always occurs at the M point regardless of the strain. The occurrence of the conduction minimum at M is consistent with the measured Fermi surface in the electron doped case, where an elliptical shaped Fermi surface has been seen [8].…”
Section: Strain Induced X Gcrossoversupporting
confidence: 87%
“…It has been suggested that the spin-orbital entanglement induced by the strong SOC in these structures could make these materials hosts for several unconventional features such as the Kitaev model [2,3], quantum spin Hall effect at room temperature [4], or unconventional superconductivity [5,6]. In addition, doped carriers in the spin-orbital entangled Mott insulating state in the iridates are expected to show many novel features and are also the subject of several recent studies [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…We use an effective on-site Coulomb interaction of U eff = 0.6eV as in the electron-doped case discussed in Ref. 19.…”
Section: Comparison To Dmft Calculationsmentioning
confidence: 99%
“…A value of η = 0.08 leads to good agreement with experiment, but hides some of the FS features that become apparent at small broadening only. There, as in the electron-doped case 19 , the Fermi surface is composed of two sheets due to the two different directions of antiferromagnetic fluctuations that are included via our cluster treatment.…”
Section: Comparison To Dmft Calculationsmentioning
confidence: 99%
“…Due to these rotations of the oxygen octahedra the unit cell is doubled and the respective Brillouin zone takes only half of the size of an undistorted geometry (C). Panels (B) and (C) adopted from Martins et al [30].…”
Section: Technique: Oriented Cluster Dynamical Mean-field Theorymentioning
confidence: 99%